ROCK Inhibitor Y27632 Induced Morphological Shift and Enhanced Neurite Outgrowth-Promoting Property of Olfactory Ensheathing Cells via YAP-Dependent Up-Regulation of L1-CAM - Li, Yijian; Huo, Shujia; Fang, Yajie; Zou, Ting; Gu, Xianliang; Tao, Qin; Xu, Haiwei (Frontiers in Cellular Neuroscience, 2018)
Olfactory ensheathing cells (OECs) are heterogeneous in morphology, antigenic profiles and functions, and these OECs subpopulations have showed different outcomes following OECs transplantation for CNS injuries. Morphologically, OECs are divided into two subpopulations, process-bearing (Schwann cells-like) and flattened (astrocytes-like) OECs, which could switch between each other reversibly and are affected by extracellular and intracellular factors. However, neither the relationship between morphology and function of OECs nor their molecular mechanisms have been clarified. In the present study, we first investigated morphological and functional differences of OECs under different cytokine exposure conditions. It demonstrated that OECs mainly displayed process-bearing shape under pro-inflammatory conditions (LPS), while displayed flattened shape under anti-inflammatory conditions (IL-4 and TGF-β1). The morphological changes were partially reversible and ROCK/F-actin pathway was involved. Functionally, process-bearing OECs under pro-inflammatory conditions showed increased cellular activity and higher migratory rate when compared with flattened OECs under anti-inflammatory conditions, and significantly promoted neurite outgrowth and extension. Remarkably, morphological shift towards process-bearing OECs induced by ROCK inhibitor Y27632 enhanced neurite outgrowth-promoting property of OECs. Furthermore, as the downstream of ROCK pathway, transcriptional co-activator YAP mediated morphological shift and enhanced neurite outgrowth-promoting property of OECs through up-regulating the expression of neural adhesion molecule L1-CAM. Our data provided evidences that OECs with specific shapes correspond to specific functional phenotypes, and opened new insights into potential combination of OECs and small-molecule ROCK inhibitors for the regeneration of CNS injuries.